Saluran Pemasaran dan Nilai Tambah Kopi Robusta di Kecamatan Wonosalam Kabupaten Jombang, Jawa Timur - Mierza Widya Syahrani; Mubarokah Mubarokah; Sri Tjondro Winarno (Universitas Merdeka Madiun, 2021)
The purpose of this study was to analyze the marketing channels and added value of Robusta coffee in Wonosalam District, Jombang Regency, East Java. The location determination is determined by purposive, where the location selection is made on a group of subjects based on the characteristics and characteristics of the production that have been previously known. Wonosalam Subdistrict, Jombang District, East Java To find out how many marketing channels there are and the amount of added value obtained from coffee processing, the Hayami method is used. The results of the study indicate that there are five marketing channels in Wonosalam District, Jombang Regency. While the margin obtained from the analysis of the added value of pure powder is Rp. 198,000, - from raw materials, the amount of margin will be distributed to production factors, consisting of 38.83% for labor income and 22.72% for other input contributions, and for a profit of 43.43%.